Optimized synthesis of nano-scale high quality HKUST-1 under mild conditions and its application in CO2 capture - Mu, Xueliang; Chen, Yipei; Lester, Edward; Wu, Tao (2018)
This study was focused on the development of an optimized method for the rapid synthesis of nano-scale HKUST-1 with high yield, high surface area and high CO2 uptake capacity but under mild conditions. A series of HKUST-1 were synthesized under different conditions, such as preparation time, temperature, activation method, etc. It was found that the nano-scale HKUST-1 MOFs (T85-3-Pm4-120) was successfully synthesized at a high yield (87%) under low temperature (85 °C) using a mixture of Triethylamine (TEA), Cu2+ and trimesic acid (TMA) with a molar ratio of 6:3:2. The highest porosity was achieved via this pristine HKUST-1 being activated (powder activation, drying at 120 °C) four times using methanol to remove impurities trapped in the pores. The best HKUST-1 MOFs (T85-3-Pm4-120) hereby prepared was then tested in CO2 adsorption and exhibited an adsorption capacity of 2.5 mmol/g. It is therefore demonstrated that the new approach proposed in this study is a rapid and effective way to synthesize highly porous HKUST-1 MOFs under mild conditions, which is of comparable surface area and CO2 uptake capacity with those MOFs prepared under harsh conditions.